Biodiversity of trematodes associated with amphibians from a variety of habitats in Corrientes Province, Argentina - Hamann, Monika Ines (2013)
The main goals of this study were to compare the richness of parasitic trematodes in amphibians with diverse habits (terrestrial, fossorial, semi-aquatic and arboreal), and to evaluate whether the composition of the trematode community is determined by ecological relationships. Specimens were collected between April 2001 and December 2006 from a common area (30 ha) in Corrientes Province, Argentina. Trematodes of amphibians in this area comprised a total of 19 species, and were dominated by common species. Larval trematodes presented highest species richness, with the metacercaria of Bursotrema tetracotyloides being dominant in the majority (78%) of the parasite communities. Adults of the trematode Catadiscus inopinatus were dominant in the majority (67%) of amphibians. The amphibians Leptodactylus latinasus, Leptodactylus bufonius and Scinax nasicus presented a high diversity of trematodes, whereas Leptodactylus chaquensis had the lowest diversity even though it presented with the highest species richness. The patterns of similarity among amphibian species showed groups linking with their habitats. Leptodactilid amphibians, with a generalist diet and an active foraging strategy showed highest infection rates with adult trematodes. The mean richness of trematode species related to host´s habitat preferences was higher in semi-aquatic amphibians. Results suggest that semi-aquatic amphibians, present in both aquatic and terrestrial environments, present a greater diversity of parasites as they have a higher rate of exposure to a wider range of prey species and, hence, to diverse infective states. The trematode composition is related to the diets and mobility of the host, and habitat.